Effectiveness of a Natural Family Planning Service Program. Issue 1 (January 2017) - Fehring, Richard J.; Schneider, Mary
Abstract: Purpose: The aims of this study were to determine and compare extended use-effectiveness of an online nurse-managed fertility education service program among women (and subgroups of women) seeking to avoid pregnancy. Study Design and Methods: This was a 24-month prospective study of a university-based online Web site with 663 nonbreastfeeding women using an online charting system to avoid pregnancy. Participants tracked their fertility online with either cervical mucus monitoring, electronic hormonal fertility monitoring, or both fertility indicators. Unintended pregnancies were validated by professional nurses. Results: Participants had a mean age of 30.4 years (SD = 6.3) and mean 1.7 children (SD = 2.0). Among the 663 nonbreastfeeding participants there were 2 unintended pregnancies per 100 at 24 cycles of correct use and 15 pregnancies at 24 cycles of typical use. However, the 212 women using the electronic fertility monitor had a typical use unintended pregnancy rate of 6 at 24 cycles of use in comparison with the 118 women using cervical mucus monitoring that had a typical use pregnancy rate of 19 at 24 cycles and with the 333 women using both fertility indicators that had a pregnancy rate of 18 at 24 cycles of use. Clinical Implications: Use of the fertility monitor to estimate fertility among nonbreastfeeding women provides the most secure method of avoiding pregnancy. Abstract : This study investigated extended use effectiveness of an online natural family planning program with non-breastfeeding women. This type of program can be effective in helping women in the United States and other countries meet their family planning goals.